The Mediating Role of Psychological Capital in The Relationship Between Ethical Leadership and Whistleblowing - Özbezek, B. Dilek; Paksoy, H. Mustafa; Paksoy, Sadettin; Gültekin, Veysel Mehmet (Fırat University, 2022)
With the global competition experienced in recent years, leaders are regarded as not only a person of power and status in an organization, but also a mentor, a motivator, a change agent, and most importantly, important sources of information that shape the attitudes and behaviors of their followers. The main purpose of this research is to determine how ethical leadership affects the whistleblowing actions of followers and whether psychological capital mediates this level of influence by making use of social learning theory and social exchange theory. Conceptual and empirical research results clearly show that ethical leadership positively affects the intention to whistleblowing by enabling employees to take the necessary initiative to raise their voices about any unethical behavior. At the same time, it has been revealed that psychological capital has a partial mediating effect in the interaction between ethical leadership and whistleblowing. The results obtained are very important in terms of pointing out new perspectives on how ethical leadership affects whistleblowing, and highlight the importance of psychological capital, which is accepted as a positive psychological resource that enables individuals to achieve their goals in business life.

Son yıllarda yaşanan küresel rekabetle birlikte, liderler bir örgütte sadece güç ve statüye sahip bir kişi değil, aynı zamanda bir mentor, bir motive edici, bir değişim ajanı ve en önemlisi takipçilerinin tutum ve davranışlarını şekillendiren önemli bilgi kaynakları olarak kabul edilmektedir. Bu araştırmanın temel amacı sosyal öğrenme teorisi ve sosyal mübadele teorisinden faydalanılarak, etik liderliğin takipçilerin bilgi uçurma eylemlerini nasıl etkilediğini ve bu etki düzeyine psikolojik sermayenin aracılık edip etmediğini tespit etmektir. Kavramsal ve ampirik araştırma sonuçları etik liderliğin, çalışanlara etik olmayan herhangi bir davranış hakkında seslerini yükseltebilmeleri için gerekli inisiyatifi almalarını sağlayarak, bilgi uçurma niyetini olumlu yönde etkilediğini açıkça göstermektedir. Bununla birlikte, psikolojik sermayenin etik liderlik ile bilgi uçurma arasındaki etkileşiminde kısmi bir aracılık etkisinin olduğu ortaya konmuştur. Elde edilen sonuçlar, gerek etik liderliğin bilgi uçurma eylemini nasıl etkilediği konusunda yeni bakış açılarına işaret edecek olması gerekse iş hayatında bireylerin hedeflere ulaşmasını sağlayan pozitif bir psikolojik kaynak olarak kabul edilen psikolojik sermayenin önemine dikkat çekmesi açısından oldukça önemlidir.
ETİK LİDERLİĞİN BİLGİ UÇURMA ÜZERİNDEKİ ETKİSİNDE PSİKOLOJİK SERMAYENİN ARACILIK ROLÜ